Alcohol Consumption and Violence among Argentine Adolescents - Mariaelena Pierobon; Mariam Barak; Sahel Hazrati; Kathryn H. Jacobsen (Elsevier, 2013)
Objective: This study investigated the association between alcohol and violence among Argentine youth. Methods: Data from the 2007 Argentina Global School-based Student Health Survey (GSHS), a nationally representative survey of middle school students, were examined using age-adjusted logistic regression models. Results: Of the 1,328 participating students aged 13 to 15 years old, 51.9% reported drinking alcohol in the previous month, with higher rates among males (p = 0.04) and older students (p < 0.01). Both male and female drinkers were nearly twice as likely as non-drinkers to report being physically attacked, being in a physical fight, and having thoughts about self-directed violence. Among drinkers, those who reported poor mental health, were victims of bullying, used tobacco or drugs, or skipped school without per- mission were approximately twice as likely as other drinkers to have engaged in violent activities. Conclusion: Public health interventions targeting violence among young adolescents should be developed in combination with alcohol education programs. Resumo: Objetivo: Este estudo investigou a associação entre álcool e violência na população de jovens argentinos. Métodos: Dados da Global School-based Student Health Survey (GSHS) de 2007, uma pesquisa representativa em termos nacionais com alunos do ensino médio, foram exami- nados utilizando-se modelos de regressão logística ajustados por idade. Resultados: Dos 1328 alunos participantes entre 13 e 15 anos de idade, 51,9% declararam ter consumido álcool no último mês, com taxas mais elevadas entre meninos (p = 0,04) e alunos mais velhos (p < 0,01). Homens e mulheres que bebem demonstraram estar quase duas vezes mais propensos a relatar agressão física, quando em uma briga física, e pensamentos sobre violência autoinfligida do que aqueles que não bebem. Entre as pessoas que bebem, aquelas que reportaram saúde mental precária, haviam sido vítimas de bullying, fumavam, faziam uso de drogas ou abandonaram a escola sem permissão se mostraram duas vezes mais propensas ao envolvimento em atividades violentas do que outras pessoas que também bebem. Conclusão: Intervenções de saúde pública quanto à violência entre jovens adolescentes devem ser desenvolvidas em combinação com programas de educação sobre álcool. Keywords: Alcohol drinking, Cross-sectional study, Adolescent, Risk factor, Violence, Argentina, Palavras-chave: Consumo de álcool, Estudo transversal, Adolescente, Fator de risco, Violência, Argentina